KONSEP-KONSEP KEGIATAN OFF-FARM - Ken Suratiyah (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1994)
Because of the increasingly limited agricultural areas, farm households could no longer depend merely on their farming products. The farmers try to obtain a double income from various off-farm resources. All of the existing family labourers -if they are still able and willing- are mobilized to join the off- farm employment for their household survivals.Off farm activities have become increasingly significant to the poorer burners, whereas for many social scientists they form substantial information which needs through attention to be able to estimate the farm honsebold income. Evenso, there has not been a uniformity of understanding among the scientists themselves about the main definition of off-farm activities. Consequently, there are varieties of meaning in analyzing farm household income coming from various sources of occupation.In this paper the author tries to present several alternatives of definition obtained from several researchers with the hope to ohtain agreements about the main definition of off-burn activities.